2020
DOI: 10.2147/cmar.s265756
|View full text |Cite
|
Sign up to set email alerts
|

<p>Value of Ultrasound Combined with Immunohistochemistry Evaluation of Central Lymph Node Metastasis for the Prognosis of Papillary Thyroid Carcinoma</p>

Abstract: Background: Papillary thyroid carcinoma (PTC) is often accompanied by cervical lymph node metastasis (LNM). The accuracy of the preoperative ultrasound diagnosis of central LNM (CLNM) is limited. LNM is a high-risk factor for local recurrence and may affect the prognosis. Factors not directly related to tumor proliferation are used for risk assessment in the tumor-node-metastasis (TNM) staging system for thyroid cancer. The present study aimed to investigate the value of ultrasound and immunohistochemistry in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Another finding was that thyroid cancer multifocality is an independent clinical characteristic related to patients with PTC with metastatic CCLNs, which is consistent with some previous reports (16,33). In our study, the multifocality rate of PTCs was found to be 48.0% in the malignant CCLN group, which was also close to that reported in the literature (16,33).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another finding was that thyroid cancer multifocality is an independent clinical characteristic related to patients with PTC with metastatic CCLNs, which is consistent with some previous reports (16,33). In our study, the multifocality rate of PTCs was found to be 48.0% in the malignant CCLN group, which was also close to that reported in the literature (16,33).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, Hashimoto’s thyroiditis was found to be an independent clinical characteristic related to patients with PTC with benign CCLNs, which was also reported in previous studies showing that the presence of Hashimoto’s thyroiditis is a protective factor for a lower incidence of cervical lymph node metastasis in patients with PTC ( 30 32 ). Another finding was that thyroid cancer multifocality is an independent clinical characteristic related to patients with PTC with metastatic CCLNs, which is consistent with some previous reports ( 16 , 33 ). In our study, the multifocality rate of PTCs was found to be 48.0% in the malignant CCLN group, which was also close to that reported in the literature ( 16 , 33 ).…”
Section: Discussionsupporting
confidence: 92%
“…Multifocality often occurs at an early stage in patients with PTC, and Yao et al 38 used multifocality as an independent risk factor for CLNM. However, some patients had microscopic PTC (an incidental finding for patients treated surgically for presumably benign thyroid diseases).…”
Section: Discussionmentioning
confidence: 99%
“…Gland metastases often occur at an early stage in patients with PTC, and multifocality is an important independent risk factor for CLNM ( 26 ). Our study indicated that multifocality is also a risk factor for CLNM in PTC ( P< 0.05), which is consistent with the findings of previous studies ( 27 ).…”
Section: Discussionmentioning
confidence: 99%